Research on Biological Activity of some Extracts from Vietnamese Carica papaya Leaves - Vien, Do Thi Hoa; Thuy, Phung Thi (ASEAN Journal of Chemical Engineering, 2012)
Carica papaya leaves have long been used in some folk remedies to treat cancer. This folk remedy originated from Queensland - Australia from 1978 (Harald W. Tietze, 1997). In Vietnam, there are some successful cases of using Carica papaya leaves for cancer treatment even though this mediation do not always work out. In this study, the soluble substances in water (aqueous extract), the carotenoid and the polar substances (polar extract) were extracted from Carica papaya leaves grown in Vietnam; the bioassays such as cytotoxicity on some tumor cell lines as well as antioxidant activity were also tested with obtained extracts. The results showed that all obtained extracts had antioxidant activity stronger than the control substance - vitamin C at the same tested concentration. At concentration of 100 μg/ml, the inhibitive activity on lung cancer cell line LU-1 of obtained extracts was highest, from 43.47% (aqueous extract) to 62.88% (polar extract). On carcinoma cell line KB, inhibitive ability of extracts was lower: 2.8% (polar extract) and 20.6% (aqueous extract). On the breast cancer cells MCF7, inhibitive ability of above extracts was quite high, from 33.95% to 56.19%. On the leukemia cell line HL 60, inhibitive ability of these extracts was also high, from 39.56 to 60.64%. In addition, the result pointed out that on stem cells isolated from mouse embryos (ESC), the obtained extracts was not toxic to healthy cells of this line. This suggested that extracts from Carica papaya leaves has the potential to become one of the natural substance products that can support cancer treatment in certain cases.